Polytetrafluoroethylene stretched porous membrane and aeration filter material and filter member using the same

KR103017847B1Active Publication Date: 2026-09-11NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020227018245
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-05
Filing Date
2020-12-03
Publication Date
2026-09-11
Estimated Expiration
2040-12-03

Smart Images

  • Figure 112022056803998-PCT00021_ABST
    Figure 112022056803998-PCT00021_ABST
Patent Text Reader

Abstract

The provided polytetrafluoroethylene stretched porous membrane has a node / fibril structure comprising a plurality of nodes and fibrils connecting the plurality of nodes. The ratio of the average length of the plurality of nodes in the thickness direction to the thickness of the stretched porous membrane is 10% or more. The stretched porous membrane is a membrane that is resistant to breakage. In the stretched porous membrane, the upper surface and lower surface have a size of 280㎛ × 280㎛, and when a rectangular parallelepiped region is assumed in which the upper surface and lower surface are respectively located on one membrane surface and the other membrane surface of the stretched porous membrane, the number of nodes per 1㎛ thickness included in the region may be 4 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a polytetrafluoroethylene (hereinafter referred to as “PTFE”) stretched porous membrane, and to an air-permeable filter material and filter member using the same. Background Technology

[0002] In the housing of various electrical products, such as automotive electronic components and portable information terminals, a filter member equipped with a ventilation filter material may be installed to cover an opening provided in the housing. The ventilation filter material has air permeability in the thickness direction while preventing the passage of foreign substances such as dust or water. By installing the filter member, ventilation through the opening can be ensured while preventing the passage of foreign substances through the opening. It is considered to use a PTFE stretched porous membrane as the ventilation filter material.

[0003] Patent Document 1 discloses a highly permeable PTFE stretched porous membrane. Patent Document 2 discloses a highly permeable PTFE stretched porous membrane having high ball rupture strength. Prior art literature

[0004] Japanese Patent Publication No. 2009-297702 and Japanese Patent Publication No. Hei 11-515036 The problem to be solved

[0005] According to a highly permeable PTFE stretched porous membrane, for example, the permeability of a filter member can be improved, thereby enabling the miniaturization of the member. However, according to the inventors' investigation, when a filter member is equipped with a highly permeable PTFE stretched porous membrane, damage such as cracking is prone to occur in the PTFE stretched porous membrane during handling or placement in a housing. Furthermore, a characteristic that makes it difficult for damage to occur is also desired for PTFE stretched porous membranes that do not have high permeability.

[0006] The present invention aims to provide a PTFE stretched porous membrane that is resistant to breakage. means of solving the problem

[0007] The present invention is,

[0008] A PTFE stretched porous membrane having a node / fibril structure comprising a plurality of nodes and fibrils connecting the plurality of nodes, and

[0009] A PTFE stretched porous membrane in which the ratio of the average length of the plurality of nodes in the thickness direction to the thickness of the stretched porous membrane is 10% or more.

[0010] It provides.

[0011] From another perspective, the present invention is,

[0012] It is a breathable filter material that has breathability in the thickness direction and prevents the passage of foreign matter in that direction, and

[0013] A breathable filter material having a PTFE stretched porous membrane according to the present invention

[0014] It provides.

[0015] From another perspective, the present invention,

[0016] It is equipped with a breathable filter material that has breathability in the thickness direction and prevents the passage of foreign matter in that direction, and

[0017] The above-mentioned aeration filter material is a filter member which is the aeration filter material of the present invention.

[0018] It provides. Effects of the invention

[0019] According to the present invention, a PTFE stretched porous membrane that is resistant to breakage is achieved. Brief explanation of the drawing

[0020] FIG. 1 is a cross-sectional view schematically illustrating an example of a PTFE stretched porous membrane of the present invention. Figure 2 is an enlarged view of the cross-section of the PTFE stretched porous membrane of Figure 1. Figure 3a is a diagram illustrating a method for evaluating the structure of a PTFE stretched porous membrane by X-ray CT. Figure 3b is a diagram illustrating a method for evaluating the structure of a PTFE stretched porous membrane by X-ray CT. FIG. 4 is a cross-sectional view schematically illustrating an example of the air-permeable filter material of the present invention. FIG. 5 is a cross-sectional view schematically illustrating another example of the aeration filter material of the present invention. FIG. 6 is a cross-sectional view schematically illustrating an example of a filter member of the present invention. FIG. 7 is a cross-sectional view schematically illustrating another example of a filter member of the present invention. FIG. 8 is a cross-sectional view schematically illustrating another example of a filter member of the present invention. FIG. 9 is a cross-sectional view schematically illustrating an example of a filter member of the present invention different from the above. FIG. 10 is a cross-sectional view schematically illustrating an example of an embodiment of supplying a filter member of the present invention. Figure 11a is an image of the surface of the PTFE stretched porous membrane of Example 1 observed by a scanning electron microscope (SEM). Figure 11b is an image of the cross-section in the thickness direction (cut in the MD direction) of the PTFE stretched porous membrane of Example 1 observed by SEM. Figure 12a is an image of the surface of the PTFE stretched porous membrane of Example 2 observed by SEM. Figure 12b is an image of the cross-section in the thickness direction (cut in the MD direction) of the PTFE stretched porous membrane of Example 2 observed by SEM. Figure 13a is an image of the surface of the PTFE stretched porous membrane of Example 3 observed by SEM. Figure 13b is an image of the cross-section in the thickness direction (cut in the MD direction) of the PTFE stretched porous membrane of Example 3 observed by SEM. Figure 14a is an image of the surface of the PTFE stretched porous membrane of Example 4 observed by SEM. Figure 14b is an image of the cross-section in the thickness direction (cut in the MD direction) of the PTFE stretched porous membrane of Example 4 observed by SEM. Figure 15a is an image of the surface of the PTFE stretched porous membrane of Comparative Example 1 observed by SEM. Figure 15b is an image of the cross-section in the thickness direction (cut in the MD direction) of the PTFE stretched porous membrane of Comparative Example 1 observed by SEM. Figure 16a is an image of the surface of the PTFE stretched porous membrane of Comparative Example 2 observed by SEM. Figure 16b is an image of the cross-section in the thickness direction (cut in the MD direction) of the PTFE stretched porous membrane of Comparative Example 2 observed by SEM. Figure 17 is a graph showing the relationship between air permeability in the thickness direction and total cohesion in PTFE stretched porous membranes of the examples and comparative examples. Specific details for implementing the invention

[0021] An example of the PTFE stretched porous membrane of the present invention is illustrated in FIG. 1. The PTFE stretched porous membrane (1) of FIG. 1 has a node / fibrill structure comprising a plurality of nodes and fibrils connecting the plurality of nodes. A node is an aggregated portion of PTFE. The PTFE stretched porous membrane (1) is typically formed by stretching a PTFE sheet. In this formation method, the portion that becomes fine fibrous (fibrillated) by stretching corresponds to a fibrill. On the other hand, the portion that is not fibrillated and maintains the aggregated state of PTFE corresponds to a node. Typically, a plurality of fibrils are connected to a single node. As illustrated in FIG. 2, in the PTFE stretched porous membrane (1), the average length L in the thickness direction of the plurality of nodes (11) with respect to the thickness T of the membrane (1) M Ratio R (=L of the average length L of the node (11) in the thickness direction) M / T) is 10% or more. In addition, FIG. 2 is an enlarged cross-sectional view of a PTFE stretched porous membrane (1) (the illustration of fibrils is omitted). The ratio R may be 12% or more, 14% or more, 15% or more, 16% or more, and furthermore 18% or more. A large ratio R means that each node (11) is extended in the thickness direction of the PTFE stretched porous membrane (1). According to the inventors' investigation, damage to the PTFE stretched porous membrane (1) that may occur, for example, when handling a filter member or when placing it in a housing, is caused by destruction (cohesive destruction) resulting from a force exceeding the cohesive force of the membrane (1) being applied to the membrane. Nodes (11) extended in the thickness direction can improve the cohesive force of the PTFE stretched porous membrane (1) and suppress cohesive destruction. Therefore, damage to the PTFE stretched porous membrane (1) is unlikely to occur.

[0022] The PTFE stretched porous membrane (1) may also have a characteristic node / fibril structure. When a rectangular region is assumed in which the upper surface and the lower surface are respectively located on one membrane surface and the other membrane surface of the PTFE stretched porous membrane (1), having upper and lower surfaces of size 280㎛×280㎛, the number N of nodes (11) per thickness of 1㎛ included in the said region is, for example, 4 or less. The number N may be 3 or less, 2 or less, 1.5 or less, 1.3 or less, 1.2 or less, 1.1 or less, 1.0 or less, and furthermore 0.9 or less. The lower limit of the number N is, for example, 0.3 or more. Conventional PTFE stretched porous membranes have a high degree of node division in the thickness direction, so they cannot achieve the above range for ratio R and number N.

[0023] Length L of the node (11) in the thickness direction, and average length L which is the average value of length L. MThe number N of the nodes (11) can be evaluated, for example, by three-dimensional image structure analysis using an X-ray CT device for the PTFE stretched porous membrane (1) (see FIG. 3a and FIG. 3b). First, a rectangular evaluation area (21) is set on the membrane (1) that includes the entire PTFE stretched porous membrane (1) in the direction parallel to the membrane surface and in the thickness direction, with a length of 280 μm × 280 μm. The thickness of the evaluation area (21) may be greater than the thickness of the PTFE stretched porous membrane (1) (see FIG. 3a), but in order to secure the resolution of the three-dimensional image to be constructed, it is preferable to make it about five times or less the thickness of the PTFE stretched porous membrane (1). In addition, if the PTFE stretched porous membrane (1) is laminated with a breathable support material such as a nonwoven fabric, the breathable support material is not included in the evaluation area (21). Next, a continuous transmission image is acquired while rotating the slice position at a predetermined interval. Rotation is performed, for example, with the MD direction of the membrane (1) as the X direction, the TD direction as the Y direction, and the thickness direction as the Z direction, about a rotation axis extending in the Z direction through the center of the main surface of the membrane (1). The number of continuous transmission images obtained is preferably 300 or more, more preferably 500 or more, even more preferably 700 or more, and particularly preferably 800 or more. Next, a three-dimensional image of the evaluation area (21) is constructed using the obtained continuous transmission images. Software attached to an X-ray CT device may be used to construct the three-dimensional image. Next, nodes (11) are extracted from the constructed three-dimensional image using image analysis software (see FIG. 3a). Nodes (11) can be extracted by the voids and other parts of the PTFE stretched porous membrane (1), typically by binarization of nodes (11) and fibrils, and separation of nodes (11) and fibrils after binarization. Binarization is performed using the Li method (CH Li and CKIt is preferable to implement it according to Lee, Minimum cross entropy thresholding, Pattern Recognition, vol.26, No.4, pp.617-625, 1993. Nodes (11) and fibrils can typically be separated by their diameters. The diameter of the node (11) may be, for example, 1 μm or more, 1.5 μm or more, 2 μm or more, or 3 μm or more. The diameter of the fibrils may be, for example, less than 1 μm, 0.8 μm or less, 0.5 μm or less, or 0.1 μm or less. In this specification, "diameter" can be defined as the length of the shortest line segment among imaginary line segments that exist only within the interior of a three-dimensional object and pass through the center of gravity of the object. Additionally, the separation of the node (11) and the fibril can be carried out in a simpler way, for example, based on the volume of the PTFE body indicated in a three-dimensional image constructed by X-ray CT, for example, when the resolution of the X-ray CT is 0.35 μm / pixel, 500 voxel (21.44 μm. 3 A PTFE body having a volume of ) or less, comprising fibrils and 500 voxel (21.44 μm) 3PTFE bodies having a volume exceeding ) may be determined as nodes, respectively. The image analysis software is, for example, ImageJ, a free software developed by the National Institutes of Health in the United States. In ImageJ, binarization by the Li method can be performed. Additionally, in ImageJ, nodes (11) and fibrils can be separated by adjusting the threshold of the noise removal command. The number N can be obtained by dividing the number of extracted nodes (11) by the thickness (unit: μm) of the PTFE stretched porous membrane (1). Next, a rectangular prism (22) (each face parallel to the XY plane, XZ plane, and YZ plane) circumscribed around each extracted node (11) is assumed in the image analysis software. The length L2 in the membrane thickness direction of the said rectangular prism (22) can be set as the length L of each said node (11) (see FIG. 3b). For all nodes (11) included in the evaluation area (21), the length L is evaluated, and the average value is the average length L. M It can be done as.

[0024] Average length L of the node (11) in the PTFE stretched porous membrane (1) M The upper limit of is, for example, 70㎛ or less, and may be 60㎛ or less, 50㎛ or less, 40㎛ or less, 30㎛ or less, and furthermore, 20㎛ or less. Average length L M The lower limit of is, for example, 5㎛ or more, 7㎛ or more, and even 9㎛ or more.

[0025] The volume fraction of the nodes (11) in the PTFE stretched porous membrane (1) may be, for example, 5% or more, 7% or more, 8.5% or more, and furthermore 10% or more. The upper limit of the volume fraction may be, for example, 30% or less, 25% or less, and furthermore 20% or less. An appropriate range of the volume fraction contributes to the achievement of a PTFE stretched porous membrane that is highly permeable and resistant to breakage. The volume fraction can be evaluated by the above three-dimensional image analysis.

[0026] The average value of the node angle α in the PTFE stretched porous membrane (1) may be, for example, 60 degrees or more, 65 degrees or more, and furthermore, 70 degrees or more. The upper limit of the average value of the node angle α may be 90 degrees or less, 85 degrees or less, and furthermore, 80 degrees or less. The appropriate range of the above average values ​​contributes to the achievement of a PTFE stretched porous membrane that is highly permeable and resistant to breakage. The node angle α is the angle formed by the major axis of an ellipse with respect to the XY plane when an ellipse with a minimum area that passes through the upper and lower ends of the node (11) and contains the node (11) is assumed on a plane selected from the XZ plane and the YZ plane where the thickness of the node (11) can be observed (in the case where stretching A is performed in the MD direction in method A described later, it is usually the XZ plane cut in the MD direction). The node angle α and its average value can be evaluated by the three-dimensional image analysis (the image of the plane can be extracted from the three-dimensional image of the evaluation area). The average value is the average value of all nodes (11) included in the evaluation area (21).

[0027] The average thickness of the nodes (11) in the PTFE stretched porous membrane (1) is, for example, 0.5 to 5 μm, and may be 1 to 3 μm. An appropriate range of average thickness contributes to the achievement of a PTFE stretched porous membrane that is highly permeable and resistant to breakage. The thickness and average thickness of the nodes (11) can be evaluated by the above three-dimensional image analysis (analysis of the plane in which the thickness of the nodes (11) can be observed among the planes selected from the XZ plane and the YZ plane). The thickness of the nodes (11) can be determined by drawing inscribed circles of the nodes (11) centered on each pixel for all pixels representing the nodes (11) on the plane, and repeating the process of leaving only the inscribed circle with a larger area when the inscribed circles overlap, histogramming the diameters of each remaining inscribed circle, and determining the average value (count average value) from the distribution of histogrammed diameters. The average thickness is the average value of the thickness of all nodes (11) included in the evaluation area (21).

[0028] The nodes (11) have a low degree of division in the thickness direction. Because of this, the PTFE stretched porous membrane (1) can have high air permeability. The air permeability of the PTFE stretched porous membrane (1) in the thickness direction is 4 cm, as indicated by Frazier air permeability. 3 / ( seconds·cm 2 It may be greater than ). The airflow in question is 4.5cm 3 / ( seconds·cm 2 ) or more, 5.0cm 3 / ( seconds·cm 2 ) or more, 6.0cm 3 / ( seconds·cm 2 ) or more, 7.0cm 3 / ( seconds·cm 2 ) Above, furthermore 8.0cm 3 / ( seconds·cm 2 It may be greater than ). The upper limit of the relevant airflow is, for example, 20.0 cm 3 / ( seconds·cm 2) is less than. In addition, the higher the permeability of the membrane, the lower the cohesive force tends to be. For this reason, when the PTFE stretched porous membrane (1) has high permeability, the effect of the present invention becomes more pronounced. However, the permeability in the in-plane direction of the PTFE stretched porous membrane (1) does not have to be high, and the membrane may have a permeability in the in-plane direction lower than, for example, the range shown above.

[0029] Frazier air permeability is determined in accordance with the air permeability measurement method A (Frasier mold method) specified in Japanese Industrial Standard (hereinafter referred to as "JIS") L1096. In addition, even if the size of the PTFE stretched porous membrane (1) is smaller than the size of the test specimen (approx. 200 mm × 200 mm) in the Frazier mold method, the Frazier air permeability can be evaluated by using a measurement jig that limits the area of ​​the measurement area. An example of a measurement jig is a resin plate having a through hole formed in the center with a cross-sectional area corresponding to the desired measurement area. For example, a measurement jig having a circular cross-section with a diameter of 1 mm or less can be used.

[0030] The PTFE stretched porous membrane (1) can have high cohesive strength (peeling cohesive strength) on average throughout the in-plane direction due to the node / fibril structure. The total cohesive strength of the PTFE stretched porous membrane (1) is 1.9 (N / 20mm). 2 It may be greater than that. In this case, the above damage can be further suppressed. The total cohesive force is represented by the product of the peeling cohesive force in the first direction within the plane of the PTFE stretched porous membrane (1) and the peeling cohesive force in the second direction orthogonal to the first direction within the plane. The first direction is, for example, the MD direction. The second direction is, for example, the TD direction. The total cohesive force is 2.0 (N / 20mm) 2 Above, 2.5 (N / 20mm) 2 Above, 2.8 (N / 20mm) 2Above, further 3.0(N / 20mm) 2 It may be greater than or equal to. The upper limit of total cohesion is, for example, 25.0 (N / 20mm) 2 Less than or equal to, 20.0 (N / 20mm) 2 Below, 15.0 (N / 20mm) 2 Below, 10.0 (N / 20mm) 2 Below, 8.0 (N / 20mm) 2 Below, furthermore 6.4 (N / 20mm) 2 It is acceptable to do the following.

[0031] A stretched PTFE porous membrane is typically formed by stretching an unstretched PTFE sheet, which is the original sheet, in two mutually orthogonal directions within the sheet plane, for example, the MD direction and the TD direction. The stretching conditions for each direction are typically different, and for this reason, the mechanical properties of the membrane are typically different between the two mutually orthogonal directions. According to the inventors' investigation, for example, when embedded in a filter member, if the membrane has high peel cohesive force in one direction but low peel cohesive force in a different direction, the membrane tends to break during handling of the member or placement in a housing. The total cohesive force is the product of the peel cohesive force in the first direction within the plane and the peel cohesive force in the second direction orthogonal to the first direction within the plane. According to the inventors' investigation, the total cohesive force is 1.9 (N / 20mm) 2 The above PTFE stretched porous membrane (1) can be judged to have high peeling cohesion on average in the in-plane direction of the membrane.

[0032] The peeling cohesive force in the first direction in the PTFE stretched porous membrane (1) may be, for example, 1.70 (N / 20mm) or more, 1.80 (N / 20mm) or more, 1.90 (N / 20mm) or more, and furthermore 2.00 (N / 20mm) or more.

[0033] The peeling cohesive force in the second direction in the PTFE stretched porous membrane (1) may be, for example, 1.15 (N / 20mm) or more, 1.20 (N / 20mm) or more, 1.40 (N / 20mm) or more, 1.50 (N / 20mm) or more, 1.60 (N / 20mm) or more, and furthermore, 1.70 (N / 20mm) or more.

[0034] The average cohesive force of the PTFE stretched porous membrane (1), represented by the average (arithmetic mean) of the peeling cohesive force in the first direction and the peeling cohesive force in the second direction, may be, for example, 1.40 (N / 20mm) or more, 1.50 (N / 20mm) or more, 1.60 (N / 20mm) or more, 1.70 (N / 20mm) or more, and furthermore, 1.80 (N / 20mm) or more.

[0035] In the PTFE stretched porous membrane (1), air permeability in the thickness direction and overall cohesiveness can coexist at a high level. The PTFE stretched porous membrane (1) has air permeability in the thickness direction P T , total cohesion C T Expressed as, Equation C T ≥-0.33×P T It may satisfy +3.67, and Equation C T ≥-0.57×P T It is okay to satisfy +6.14.

[0036] In this specification, PTFE includes modified PTFE. In other words, the PTFE stretched porous membrane (1) includes a stretched porous membrane of modified PTFE. Modified PTFE is a copolymer of tetrafluoroethylene (hereinafter referred to as “TFE”) and a modified comonomer. The content of TFE units in the copolymer is, for example, 95 mass% or more, preferably 97 mass% or more, and more preferably 99 mass% or more. The modified comonomer is, for example, at least one selected from ethylene, perfluoroalkyl vinyl ether, hexafluoropropylene, and perfluoromethyl vinyl ether. However, modified PTFE may be excluded from PTFE. In other words, PTFE may be unmodified PTFE (a homopolymer of TFE).

[0037] The standard specific gravity (SSG) of PTFE may be 2.18 or less. The SSG is specified in JIS K6935-1.

[0038] The weight per unit area of ​​the PTFE stretched porous membrane (1) is, for example, 1.0 g / m² 2 That is all, 7.0g / m² 2 Above, 8.0g / m² 2 Above, 10.0g / m² 2 Above, 12.0g / m² 2 Above, furthermore 13.0 g / m 2 It may be greater than or equal to. The upper limit of weight per unit area is, for example, 87.2 g / m² 2 The following applies. The weight per unit area can be calculated by dividing the weight of the PTFE stretched porous membrane (1) by the area of ​​the main surface.

[0039] The thickness of the PTFE stretched porous film (1) may be, for example, 10 μm or more, 30 μm or more, 35 μm or more, 40 μm or more, and furthermore 45 μm or more. The upper limit of the thickness may be, for example, 200 μm or less, and may be 100 μm or less.

[0040] The porosity of the PTFE stretched porous membrane (1) may be, for example, 80% or more, 85% or more, 88% or more, and furthermore, 90% or more. The upper limit of the porosity is, for example, 99% or less. The porosity can be calculated by substituting the mass, thickness, area (surface area), and true density of PTFE of the membrane into the following formula. In addition, the true density of PTFE is 2.18 g / cm³ 3 am.

[0041] Porosity (%) = {1 - (mass [g] / (thickness [cm] × area [cm²]} 2 ]×True density[g / cm² 3 ]))}×100

[0042] The bulk density of the PTFE stretched porous membrane (1) is, for example, 0.30 g / cm³ 3 Below, 0.25g / cm³ 3 Below, 0.20g / cm³ 3 Below, 0.19 g / cm³ 3 Below, 0.18 g / cm³ 3 Below, 0.16 g / cm³ 3 Below, furthermore 0.15 g / cm³ 3 It may be less than or equal to this. The lower limit of bulk density is, for example, 0.08 g / cm³. 3 That is all. An appropriate range of bulk density contributes to the achievement of a PTFE stretched porous membrane that is highly permeable and resistant to breakage. The bulk density can be obtained from the weight and thickness per unit area of ​​the PTFE stretched porous membrane (1).

[0043] The water pressure resistance (limit water pressure resistance) of the PTFE stretched porous membrane (1) may be, for example, 30 kPa or more, 35 kPa or more, 40 kPa or more, 44 kPa or more, and furthermore 50 kPa or more. The upper limit of the water pressure resistance is, for example, 500 kPa or less. The water pressure resistance can be measured as follows by using a measuring jig in accordance with the water resistance test method A (low pressure method) or method B (high pressure method) specified in JIS L1092.

[0044] An example of a measuring jig is a stainless steel disc with a diameter of 47 mm, having a through hole (with a circular cross-section) with a diameter of 1 mm in the center. This disc has a thickness that is not deformed by the water pressure applied when measuring water pressure. The measurement of water pressure using this measuring jig can be performed as follows.

[0045] A PTFE stretched porous membrane (1) to be evaluated is fixed to one side of the measuring jig to cover the opening of the through hole of the measuring jig. The fixing is done so that water does not leak from the fixed part of the membrane during the measurement of water pressure resistance. For fixing the membrane, a double-sided adhesive tape with a water passage hole punched in the center having a shape matching the shape of the opening may be used. The double-sided adhesive tape should be placed between the measuring jig and the membrane so that the circumference of the water passage hole matches the circumference of the opening. Next, the measuring jig with the membrane fixed is set in a test device such that the side opposite to the fixed surface of the membrane becomes the surface for applying water pressure during measurement, and the water pressure resistance is measured according to the water resistance test method A (low water pressure method) or method B (high water pressure method) of JIS L1092. However, the water pressure resistance is measured based on the water pressure when water comes out from one spot on the membrane surface of the PTFE stretched porous membrane (1). The measured water pressure can be the water pressure of the PTFE stretched porous membrane (1). For the test device, a device having a configuration similar to the water resistance test device exemplified in JIS L1092 and a test specimen mounting structure capable of setting the measurement jig can be used.

[0046] The PTFE stretched porous membrane (1) may be a single layer membrane.

[0047] The PTFE stretched porous membrane (1) may be subjected to liquid-repellent treatment, such as water-repellent treatment and oil-repellent treatment. Liquid-repellent treatment can be performed by coating with a liquid-repellent material such as a fluorine-based compound. Known methods may be employed for the coating.

[0048] The PTFE stretched porous membrane (1) may be subjected to a coloring treatment. The coloring treatment may be performed, for example, by dyeing the PTFE stretched porous membrane (1) or by including a coloring agent in the PTFE stretched porous membrane (1). The coloring treatment may be performed such that light having a wavelength in the range of 380 to 500 nm is absorbed. In this case, the PTFE stretched porous membrane (1) may be colored blue, gray, brown, pink, green, yellow, etc.

[0049] The PTFE stretched porous membrane (1) can be used as a breathable filter material that, for example, has breathability in the thickness direction and prevents the passage of foreign matter in that direction. Examples of foreign matter include particles such as dust and liquids such as water droplets. However, the use of the PTFE stretched porous membrane (1) is not limited to the above examples.

[0050] The PTFE stretched porous membrane (1) can be manufactured, for example, by the following method A. The PTFE stretched porous membrane (1) may be a membrane obtained by method A. However, the method of manufacturing the PTFE stretched porous membrane (1) is not limited to method A.

[0051] [Method A]

[0052] A microscopic PTFE sheet is stretched in a predetermined direction at a stretching temperature below the melting point of PTFE (stretch A);

[0053] The sheet that has undergone stretching A is fired at a temperature above the melting point of PTFE (firing B);

[0054] The sheet that has undergone firing B is further stretched in a direction different from the above-mentioned predetermined direction at a stretching temperature below the melting point of PTFE (stretching C).

[0055] (Yeonshin A)

[0056] In stretching A, a micro-PTFE sheet is stretched in a predetermined direction at a stretching temperature below the melting point of PTFE (the melting point of the crystal, 343°C). Stretching A may be performed, for example, in a heating furnace controlled to the temperature (stretching temperature) at which stretching A is performed. Stretching A may be performed, for example, by roll stretching. However, the method of performing stretching A is not limited to the above examples.

[0057] The stretching temperature of stretching A is, for example, 200 to 340°C, and may be 280 to 330°C.

[0058] The elongation ratio of elongation A is, for example, 1.5 to 10.0 times, and may be 2.0 to 8.0 times. When air permeability in the thickness direction and overall cohesiveness are combined at a higher level, the elongation ratio is preferably 4.0 to 5.0 times. When water pressure resistance is improved while air permeability in the thickness direction and overall cohesiveness are combined at a high level, the elongation ratio is preferably 3.0 to 4.0 times.

[0059] The direction of stretching A (a predetermined direction) is, for example, the MD direction of the PTFE sheet. If the PTFE sheet is strip-shaped, the direction of stretching A may be the length direction of the PTFE sheet.

[0060] It is preferable to perform stretching A while suppressing the degree of stretching per hour. It is believed that suppressed stretching A contributes to the formation of the PTFE stretched porous membrane (1) having the node / fibril structure. According to the inventors' investigation, there is a tendency for nodes (11) that are extended not only in the in-plane direction but also in the thickness direction of the membrane to be formed by suppressed stretching A and subsequent firing B. Suppressed stretching can be performed, for example, by reducing the stretching ratio per hour. The stretching ratio per hour is indicated by the deformation rate, for example, 0.5 to 5.0 / min, 0.5 to 3.0 / min, 0.5 to 2.0 / min, and furthermore, 0.5 to 1.9 / min. The deformation rate can be obtained by dividing the stretching speed (m / min) by the stretching distance (m). The deformation rate is typically kept constant during stretching A.

[0061] (Fire B)

[0062] In firing B, the sheet that has undergone stretching A is fired at a temperature above the melting point of PTFE. Firing B can be carried out, for example, in a furnace controlled to a temperature (firing temperature) at which firing B is carried out.

[0063] The firing temperature is, for example, 350 to 400°C, and may be 355 to 395°C. The firing time is, for example, 10 to 40 seconds, and may be 12 to 38 seconds.

[0064] It is preferable to perform firing B in a state where the sheet is not stretched. It is presumed that performing firing in this state between stretching A and stretching C contributes to the formation of the PTFE stretched porous material having the node / fibril structure. According to the inventors' examination, the nodes (11) formed by stretching A are heat-set by firing B, and thereby the structure of the nodes (11) is maintained even by stretching C, which expands the gaps between the fibrils. However, slight stretching or shrinkage is permitted to correct loosening or elongation of the sheet that may occur due to changes in temperature. The stretching ratio permitted in firing B is, for example, 0.80 to 2.00 times, and 0.90 to 1.10 times is preferred. A stretching ratio of less than 1 indicates shrinkage. Furthermore, the PTFE stretched porous film (1) obtained through firing B is a fired film. In this regard, the PTFE stretched porous membrane (1) may be a sintered membrane.

[0065] (Yeonsin C)

[0066] In stretching C, the sheet that has undergone firing B is further stretched in a direction different from the above-mentioned predetermined direction at a stretching temperature below the melting point of PTFE. Stretching C can be performed, for example, in a heating furnace controlled to the temperature (stretching temperature) at which stretching C is performed. Stretching C can be performed, for example, by tenter stretching. However, the method of performing stretching C is not limited to the above examples.

[0067] The stretching temperature of stretching C is, for example, 40 to 340°C, and may be 100 to 330°C.

[0068] The elongation ratio of elongation C is, for example, 2 to 15 times, and may be 4 to 10 times.

[0069] The direction of stretching C is typically approximately perpendicular to the direction of stretching A within the sheet plane. The direction of stretching C is, for example, the TD direction of the PTFE sheet. If the PTFE sheet is strip-shaped, the direction of stretching C may be the width direction of the PTFE sheet.

[0070] In Method A, other stretching methods other than Stretch A and Stretch C may be performed as needed. However, it is preferable that the initial stretching performed on the PTFE sheet is Stretch A. In Method A, only Stretch A and Stretch C may be performed as stretching of the PTFE sheet. Stretch A, Sintering B, and Stretch C may be performed continuously.

[0071] The PTFE stretched porous membrane (1) obtained by method A is typically a biaxially stretched membrane. In this respect, the PTFE stretched porous membrane (1) may be a biaxially stretched membrane.

[0072] The microscopic PTFE sheet provided in Method A can be formed, for example, by forming a mixture of PTFE fine powder and a liquid lubricant into a sheet shape by extrusion and / or rolling. It is preferable to remove the liquid lubricant from the PTFE sheet before stretching A by means such as heating or extraction. Furthermore, it is preferable not to apply a compressive force in the thickness direction of the microscopic PTFE sheet after removing the liquid lubricant; in other words, it is preferable to stretch a PTFE sheet (non-densified sheet) that has not undergone densification by the application of the compressive force.

[0073] For PTFE fine powder, commercially available products such as Polyfron F-104 (Daikin Kogyo), Fluon CD-123E, Fluon CD-145E (AGC), and Teflon 6J (Mitsui Kemmers Fluoro Products) can be used.

[0074] Examples of liquid lubricants include liquid paraffin, naphtha, white oil, hydrocarbon oils such as toluene and xylene, various alcohols, ketones, and esters. However, the liquid lubricant is not limited to the above examples as long as it is possible to wet the surface of the PTFE fine powder and remove the mixture after forming it into a sheet.

[0075] The mixing ratio of PTFE fine powder and liquid lubricant is typically about 5 to 50 parts by weight of liquid lubricant per 100 parts by weight of PTFE fine powder.

[0076] The thickness of the microscopic PTFE sheet can be adjusted according to the desired thickness of the PTFE stretched porous membrane (1), for example, about 0.05 to 0.5 mm.

[0077] In Method A, any process may be performed after stretching C as needed. An example of a process is heat setting, which involves holding the sheet at a temperature above the melting point of PTFE. By heat setting, the structure of the stretched sheet is maintained. Heat setting may be performed in the same manner as firing B. Heat setting may be performed continuously following stretching C.

[0078] [Aeration filter media]

[0079] An example of the air-permeable filter material of the present invention is illustrated in FIG. 4. The air-permeable filter material (2 (2A)) of FIG. 4 comprises a PTFE stretched porous membrane (1). Another example of the air-permeable filter material of the present invention is illustrated in FIG. 5. The air-permeable filter material (2 (2B)) of FIG. 5 further comprises a breathable support material (3). The breathable support material (3) is laminated onto the PTFE stretched porous membrane. The breathable support material (3) can improve the strength and handling properties of the air-permeable filter material (2).

[0080] The breathable support material (3) typically has high breathability in the thickness direction compared to the PTFE stretched porous membrane (1). Examples of the breathable support material (3) are woven fabrics, nonwoven fabrics, nets, and meshes. Examples of materials constituting the breathable support material (3) include polyesters such as polyethylene terephthalate (PET), polyolefins such as polyethylene (PE) and polypropylene (PP), and aramid resins. The shape of the breathable support material (3) may be the same as or different from the shape of the PTFE stretched porous membrane (1) when viewed perpendicularly to the main surface of the breathable filter material (2). The breathable support material (3) may have a shape corresponding to the periphery of the PTFE stretched porous membrane (1) when viewed perpendicularly to the main surface of the breathable filter material (2). If the shape of the PTFE stretched porous membrane (1) is circular, the shape is a ring shape. The composition and shape of the breathable support material (3) are not limited to the above examples.

[0081] The air-permeable filter material (2B) is provided with one air-permeable support material (3) disposed on one side of the PTFE stretched porous membrane (1). The air-permeable filter material (2) may be provided with two or more air-permeable support materials (3). In the air-permeable filter material (2), air-permeable support materials (3) may be disposed on both sides of the PTFE stretched porous membrane (1). The PTFE stretched porous membrane (1) and the air-permeable support material (3) may be joined by welding, such as thermal welding and ultrasonic welding, or by an adhesive or adhesive.

[0082] The ventilation filter material (2) may have any layer and / or member other than that described above.

[0083] The thickness of the air filter material (2) is, for example, 10 to 300 μm, and may be 50 to 200 μm.

[0084] The weight per unit area of ​​the aeration filter material (2) is, for example, 1.0 to 200.0 g / m² 2 and 10.0 to 100.0 g / m² 2 It is okay to continue.

[0085] The air-permeable filter material (2) may have the same characteristics as the PTFE stretched porous membrane (1), for example, air permeability in the thickness direction and / or water pressure resistance.

[0086] The aeration filter material (2) may be treated with liquid removal and / or coloring.

[0087] The shape of the aeration filter material (2) is, when viewed perpendicularly to the main surface of the aeration filter material (2), a polygon including, for example, a square and a rectangle, a circle, an ellipse, or a strip. The corners of the polygon may be rounded. However, the shape of the aeration filter material (2) is not limited to the above examples. The strip-shaped aeration filter material (2) may be wound to form a wound body. Additionally, if necessary, it may be wound in a laminated state with a release sheet (separator).

[0088] The area of ​​the single-leaf air-permeable filter material (2) having the shape of a polygon, circle, ellipse, etc., is 675 mm 2 It may be less than 175mm 2 It may be less than or equal to. The lower limit of the area is, for example, 0.20mm 2 That is all. The air-permeable filter material (2) having the said area is suitable for use in a miniaturized filter member. However, the area of ​​the air-permeable filter material (2) may be larger depending on the application.

[0089] The aeration filter material (2) can be used, for example, in a filter member. However, the use of the aeration filter material (2) is not limited to the above examples.

[0090] [Filter Absence]

[0091] An example of a filter member of the present invention is illustrated in FIG. 6. The filter member (4(4A)) of FIG. 6 is a ventilation filter material that has air permeability in the thickness direction and prevents the passage of foreign matter in that direction, and is equipped with the ventilation filter material (2) described above. The filter member (4A) is a member that is disposed on the surface of an object having a surface having an opening, for example, to prevent the passage of foreign matter through the opening while ensuring air permeability through the opening. In this case, the filter member (4A) is typically disposed such that the ventilation filter material (2) covers the opening of the object.

[0092] The filter member (4A) has an adhesive layer (5) disposed on one side of the air-permeable filter material (2). The air-permeable filter material (2) and the adhesive layer (5) are directly bonded. The filter member (4A) can be disposed on the surface of the object through the adhesive layer (5).

[0093] When handling the filter member (4) and placing it on an object, a strong force may be applied to the member (4) in a specific direction. However, the air-permeable filter material (2) is provided with a PTFE stretched porous membrane (1) that has a specific node / fibril structure and can exhibit high overall cohesive force. Therefore, for example, the filter member (4) can be manufactured without limiting the direction of insertion of the air-permeable filter material (2) (or PTFE stretched porous membrane (1)) into the filter member (4).

[0094] Examples of adhesives constituting the adhesive layer (5) include acrylic adhesives, silicone adhesives, urethane adhesives, epoxy adhesives, and rubber adhesives. If it is necessary to consider the use of the filter member (4) under high temperature, it is preferable to select an acrylic adhesive or a silicone adhesive, particularly a silicone adhesive, which has excellent heat resistance. The adhesive layer (5) may be a double-sided adhesive tape without a substrate. The adhesive may be a curable adhesive such as phenolic resin, epoxy resin, urea resin, polyurethane resin, melamine resin, and polyester resin.

[0095] The outer circumference of the air-permeable filter material (2) and the outer circumference of the adhesive layer (5) coincide when viewed perpendicularly to the main surface of the air-permeable filter material (2). Additionally, the shape of the adhesive layer (5) corresponds to the periphery of the air-permeable filter material (2) when viewed perpendicularly to the main surface of the air-permeable filter material (2). The area of ​​the air-permeable filter material (2) where the adhesive layer (5) is not bonded can be designated as the air-permeable area of ​​the filter member (4A). However, the shape of the adhesive layer (5) is not limited to the above example.

[0096] The area of ​​the ventilation zone is, for example, 40mm 2 The following applies. A filter member (4) having an air circulation area within the specified range is suitable for placement, for example, in an object having a small-diameter opening. The lower limit of the air circulation area is, for example, 0.008 mm. 2 That is all. However, the area of ​​the ventilation zone may be larger depending on the type of object on which the filter member (4) is placed.

[0097] A modified example of the filter member (4) is shown below. The filter member (4(4B)) of FIG. 7 has the same configuration as the filter member (4A), except that it further comprises a substrate layer (6) disposed on one side of the air-permeable filter material (2), and the air-permeable filter material (2) and the adhesive layer (5) are bonded together through the substrate layer (6). The substrate layer (6) can improve the strength and handling of the filter member (4) and can suppress damage to the air-permeable filter material (2) during handling or placement on an object.

[0098] Examples of materials constituting the substrate layer (6) include polyolefins such as PE and PP, polyesters such as PET, silicone resin, polycarbonate, polyimide, polyamideimide, polyphenylene sulfide, polyetheretherketone (PEEK), polyvinyl chloride, fluoropolymer, and metals such as aluminum and stainless steel. Examples of fluoropolymers include PTFE, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and tetrafluoroethylene-ethylene copolymer (ETFE). However, the materials constituting the substrate layer (6) are not limited to the above examples.

[0099] The outer circumference of the air-permeable filter material (2) and the outer circumference of the substrate layer (6) coincide when viewed perpendicularly to the main surface of the air-permeable filter material (2). Additionally, the shape of the substrate layer (6) corresponds to the periphery of the air-permeable filter material (2) when viewed perpendicularly to the main surface of the air-permeable filter material (2). The area of ​​the air-permeable filter material (2) where the substrate layer (6) is not bonded can be designated as the air-permeable area of ​​the filter member (4B). However, the shape of the substrate layer (6) is not limited to the above example.

[0100] The air-permeable filter material (2) and the substrate layer (6) may be joined by an adhesive or adhesive, or by welding such as thermal welding or ultrasonic welding. The air-permeable filter material (2) and the substrate layer (6) may be joined by an adhesive layer. The adhesive layer may have the same composition as the adhesive layer (5). The substrate layer (6) and the adhesive layer (5) may each be the substrate and adhesive layer of a single-sided adhesive tape or a double-sided adhesive tape.

[0101] The filter member (4(4C)) of FIG. 8 has the same configuration as the filter member (4B), except that it further comprises a substrate layer (6(6B)) disposed on the other side of the air-permeable filter material (2). The air-permeable filter material (2) is supported by being fitted between a pair of substrate layers (6(6A, 6B)). This fitted support structure can further improve the strength and handling of the filter member (4).

[0102] The filter member (4(4D)) of FIG. 9 has the same configuration as the filter member (4C), except that it further comprises a tab film (7) and the base layer (6(6B)) and the tab film (7) are bonded together via an adhesive layer (5(5B)). The tab film (7) has a tab that protrudes outwardly from the outer circumference of the base layer (6B) when viewed perpendicularly to the main surface of the base layer (6B). The filter member (4D) can be handled or placed on the surface of an object by gripping the tab. The tab film (7) is typically removed when the filter member (4D) is used. The tab film (7) may be composed of the same material as the material constituting the base layer (6). Additionally, the tab film (7) is typically removed by gripping the tab and lifting it up. At this time, a strong force is applied to the air-permeable filter material (2) in the lifting direction.

[0103] The filter member (4) can be supplied, for example, by a sheet for supplying members. An example of a member supply assembly, which is a supply mode of the filter member (4) by said sheet, is illustrated in FIG. 10. The member supply assembly (10) of FIG. 10 comprises a sheet (9) for supplying members and a filter member (4 (4D)) disposed on the sheet (9). The filter member (4) is disposed on the sheet (9) via an adhesive layer (5 (5A)). According to the member supply assembly (10), the filter member (4) can be efficiently supplied for, for example, a process of placing it on the surface of an object. A plurality of filter members (4) may be disposed on the sheet (9).

[0104] The filter member (4) may be disposed on the sheet (9) via an adhesive layer provided on the placement surface of the filter member (4) in the sheet (9). It is preferable that the adhesive layer on the placement surface be weakly adhesive.

[0105] Since the PTFE stretched porous membrane (1) is unlikely to be damaged, depending on the configuration of the filter member (4), for example, it is possible to lift and peel off the filter member (4) from the sheet (9) without damaging the membrane (1).

[0106] Examples of materials constituting the sheet (9) include paper, metal, resin, and composite materials thereof. Metals include, for example, stainless steel and aluminum. Resins include, for example, polyester such as PET, and polyolefins such as PE and PP. However, the materials constituting the sheet (9) are not limited to the above examples. The sheet (9) may be in the form of a single sheet or a strip. If the sheet (9) is in the form of a strip, the material supply assembly (10) may be wound to form a wound body.

[0107] Examples of objects on which the filter member (4) is placed include housings of electronic devices and housings of automotive electronic components. The filter member (4) may be placed on the outer surface and / or inner surface of the housing. In this case, the opening may be a ventilation opening and / or a sound opening provided in the housing. Examples of electronic devices include wearable devices such as smartwatches and wristbands; various cameras including action cameras and security cameras; information and communication devices such as mobile phones, smartphones, and tablets; virtual reality (VR) devices; augmented reality (AR) devices; and sensor devices. Examples of automotive electronic components include lamps and ECUs. However, the objects are not limited to the above examples.

[0108] The foreign matter that is prevented from passing by the arrangement of the filter member (4) is, for example, particles such as dust, liquid water such as water droplets.

[0109] Examples

[0110] The present invention will be explained in more detail below by way of examples. The present invention is not limited to the following examples.

[0111] This describes a method for evaluating PTFE stretched porous membranes.

[0112] [Weight per unit area]

[0113] The weight per unit area was calculated by the method described above.

[0114] [structure]

[0115] Average length of nodes L MAs described above, the number of nodes N, the volume fraction of the nodes, the average value of the node angle α, and the average thickness of the nodes were evaluated by three-dimensional image analysis using an X-ray CT device. A Zeiss Xradia 520 Versa was used as the X-ray CT device. ImageJ (Ver. 1.47r) was used as the image analysis software. The observation conditions for the X-ray CT were set to CuKα rays, tube voltage 60 kV, tube current 83 μA, and resolution 0.35 μm / pixel. The size of the evaluation area (21) was set to 280 μm × 280 μm in the direction parallel to the film surface and 140 μm in the thickness direction (including the entire film of the evaluation target in the thickness direction). 1601 continuous transmission images were acquired to construct a three-dimensional image of the evaluation area. Binarization in the image analysis software was based on the Li method. In addition, the separation of nodes and fibrils is 500 voxel (21.44 µm). 3 A PTFE body having a volume of ) or less was determined to be a fibrill, and the noise removal command was performed by adjusting the threshold.

[0116] [thickness]

[0117] Ten random images of the YZ plane were extracted from the three-dimensional image constructed by the above X-ray CT, and the average value of the thickness obtained from the extracted plane images was taken as the thickness of the PTFE stretched porous membrane.

[0118] [Water Pressure (Limit Water Pressure)]

[0119] The water pressure resistance was determined by the method described above in accordance with the provisions of the water resistance test method B (high pressure method) specified in JIS L1092.

[0120] [Porosity]

[0121] The porosity was calculated by the method described above.

[0122] [Breathability in the thickness direction]

[0123] The air permeability in the thickness direction (Frasier air permeability) was obtained by the above-described method in accordance with the specifications of the air permeability measurement method A set forth in JIS L1096.

[0124] [Total Cohesion]

[0125] The total cohesive force was determined by the following method. First, the PTFE stretched porous membrane to be measured was cut into a rectangle (length 150 mm × width 20 mm). Next, two double-sided adhesive tapes (Nitto Denko, No. 5610) having the same shape as the PTFE stretched porous membrane were prepared. Next, each double-sided adhesive tape was bonded to one side and the other side of the PTFE stretched porous membrane by aligning their outer peripheries. Next, two rectangular PET films (Toray, Lumirror S10#25, thickness 25 μm) with length 200 mm × width 20 mm were prepared, and each PET film was bonded to one side and the other side of the PTFE stretched porous membrane by the above double-sided adhesive tapes. The bonding of the PET films was performed such that both ends in the width direction of each PET film coincided with both ends in the width direction of the PTFE stretched porous membrane, and one end in the length direction of each PET film coincided with one end in the length direction of the PTFE stretched porous membrane. As a result, a length (50 mm) was secured at the other end in the length direction of the PET film, allowing the chuck of the tensile testing machine to stably grip the PET film. Next, a compression roller with a load of 19.6 N was reciprocated once to apply a compressive force in the thickness direction of the laminate of PET film / double-sided adhesive tape / PTFE stretched porous membrane / double-sided adhesive tape / PET film. Subsequently, the specimen was left at room temperature for 12 hours and then at 60°C for 1 hour until the tensile test was started to obtain the specimen. In addition, regarding the same PTFE stretched porous membrane, a specimen S was cut by aligning the longer side in the MD direction of the membrane. MD Wow, test specimen S cut with the longer side aligned in the TD direction of the membrane.TD prepared.

[0126] Next, a tensile testing machine (A&D, Tensilon Universal Testing Machine RTF) was prepared. The test specimens were held horizontally, and one free end of the PET film was bent upward and installed on the upper chuck of the tensile testing machine, while the other free end of the PET film was bent downward and installed on the lower chuck of the tensile testing machine. Next, under conditions of a measurement temperature of 23±5℃, a measurement humidity of 50±5% RH, and a tensile speed of 300 mm / min, a tensile test (T-peel test) was performed by stretching one free end of the PET film upward and the other free end of the PET film downward to induce cohesive fracture in the stretched porous PTFE film. After the displacement of the PET film due to cohesive fracture began, the intercalation stress measured at an initial displacement of 25 mm was ignored, and the average value of the continuously recorded stress measurements at a subsequent displacement of 50 mm was defined as the peel cohesive force (unit: N / 20 mm) of the stretched PTFE porous membrane. Specimen S MD From this, the peel cohesion in the MD direction was calculated. Test specimen S TD From this, the peeling cohesive force in the TD direction was calculated. Next, the total cohesive force was calculated as the product of the peeling cohesive forces on both sides.

[0127] (Example 1)

[0128] A PTFE paste was formed by uniformly mixing 100 parts by weight of PTFE fine powder (unmodified, standard specific gravity (SSG) 2.16) and 19.7 parts by weight of an aliphatic hydrocarbon as a liquid lubricant. Next, the formed PTFE paste was subjected to 2.5 MPa (25 kg / cm²) using an FT die. 2 It was extruded into a sheet under pressure and further rolled by a pair of metal rolls to obtain a strip-shaped PTFE sheet (unoriented, thickness 0.2 mm) with adjusted thickness. Next, the obtained PTFE sheet was heated to remove the liquid lubricant.

[0129] Next, while continuously feeding the PTFE sheet, it was uniaxially stretched in the longitudinal direction in a heating furnace maintained at 300°C (stretch A). The stretching ratio was set to 3.5 times. Stretch A was performed by roll stretching, and the deformation speed was set to 1.78 / min.

[0130] Next, the sheet after stretching A was fired by passing it through a heating furnace maintained at 375°C without stretching (firing B). The time of passage through the heating furnace was set to 17 seconds.

[0131] Next, the sheet after firing B was uniaxially stretched in the width direction in a furnace maintained at 330°C (stretch C). The stretching ratio was set to 10 times. Stretch C was performed by tenter stretching. The area stretching ratio of Example 1 was 35 times. Next, the sheet after stretching C was heat-set by passing it through a furnace maintained at 380°C without stretching, thereby obtaining a stretched PTFE porous membrane.

[0132] (Examples 2 to 4)

[0133] PTFE stretched porous membranes of Examples 2 to 4 were obtained in the same manner as Example 1, except that the conditions for stretching A, firing B, stretching C, and heat setting were set as shown in Table 1 below. In addition, the conditions of Example 1 are also shown in Table 1.

[0134]

[0135] (Comparative Example 1)

[0136] An unoriented PTFE sheet prepared in the same manner as in Example 1 was continuously fed and uniaxially stretched in the longitudinal direction in a heating furnace maintained at 375°C (stretch D). The stretching ratio was set to 4.5 times. Stretch D was performed by roll stretching, and the strain rate was set to 1.94 / min.

[0137] Next, without performing sintering, the sheet after stretching D was uniaxially stretched in the width direction in a furnace maintained at 330°C (stretching G). The stretching ratio was set to 10 times. Stretching G was performed by tenter stretching. The area stretching ratio of Comparative Example 1 was 45 times. Next, the sheet after stretching G was heat-set by passing it through a furnace maintained at 380°C without stretching, thereby obtaining a stretched PTFE porous membrane. The conditions of Comparative Example 2 are summarized in Table 2 below.

[0138] (Comparative Example 2)

[0139] A PTFE stretched porous membrane of Comparative Example 2 was obtained in the same manner as Comparative Example 1, except that SSG 2.19 was used as the PTFE fine powder and the conditions of stretching D, stretching G, and heat setting were set to the conditions shown in Table 2 below.

[0140]

[0141] SEM images of the surface of each PTFE stretched porous membrane are shown in FIGS. 11a to 16a, respectively. SEM images of the cross-section in the thickness direction (cut in the MD direction) of each PTFE stretched porous membrane are shown in FIGS. 11b to 16b, respectively. In addition, the evaluation substrate used for SEM observation is shown together with the PTFE stretched porous membrane in the cross-sectional SEM images. As shown in FIGS. 11a to 16b, unlike the membrane of the comparative example, the PTFE stretched porous membrane of the example had nodes formed that were extended not only in the in-plane direction but also in the thickness direction of the membrane.

[0142] The evaluation results of each PTFE stretched porous membrane are shown in Tables 3 and 4 below.

[0143]

[0144]

[0145] As shown in Table 3, the average node length L in the PTFE stretched porous membrane of the example. M The value was larger compared to the membrane of the comparative example. The number of nodes N of the PTFE stretched porous membrane of the example was smaller compared to the membrane of the comparative example. The average value of the node angle α in the PTFE stretched porous membrane of the example was larger compared to the membrane of the comparative example; in other words, the nodes of the PTFE stretched porous membrane of the example were in an upright state along the thickness direction of the membrane. Meanwhile, no significant difference was observed in the volume fraction and thickness of the nodes between the example and Comparative Example 1. As shown in Table 4, in the PTFE stretched porous membrane of the example, a high level of compatibility in air permeability in the thickness direction and overall cohesiveness was achieved compared to the membrane of the comparative example.

[0146] Figure 17 illustrates the relationship between air permeability in the thickness direction and total cohesive force in the PTFE stretched porous membranes of the example and comparative example. As shown in Figure 17, the PTFE stretched porous membrane of the example had higher air permeability and total cohesive force compared to that of the comparative example. In addition, the PTFE stretched porous membrane of the example had an air permeability in the thickness direction P T , total cohesion C T Expressed as, Equation C T ≥-0.33×P T It satisfied +3.67. The PTFE stretched porous membranes of Examples 2 and 3 were formula C T ≥-0.57×P T It was satisfying +6.14. Industrial applicability

[0147] The PTFE stretched porous membrane of the present invention can be used, for example, as an aeration filter material.

Claims

Claim 1 A polytetrafluoroethylene stretched porous membrane having a node / fibril structure comprising a plurality of nodes and fibrils connecting the plurality of nodes, wherein the ratio of the average length of the plurality of nodes in the thickness direction to the thickness of the stretched porous membrane is 10% or more, the average thickness of the nodes in the stretched porous membrane is 0.5 to 5 μm, and at the same time, the average value of the node angle α is 60 degrees or more and 80 degrees or less. Claim 2 A polytetrafluoroethylene stretched porous membrane having an upper surface and a lower surface of size 280㎛×280㎛, wherein, when a rectangular parallelepiped region is assumed in which the upper surface and the lower surface are respectively located on one membrane surface and the other membrane surface of the stretched porous membrane, the number of nodes per 1㎛ thickness included in the said region is 4 or less. Claim 3 In claim 1 or 2, the air permeability in the thickness direction is indicated by Frazier air permeability, 4 cm 3 / ( seconds·cm 2 Polytetrafluoroethylene stretched porous membrane with more than ) Claim 4 In claim 1 or 2, the total cohesive force, represented by the product of the peeling cohesive force in the first direction within the plane and the peeling cohesive force in the second direction orthogonal to the first direction within the plane, is 1.9 (N / 20mm). 2 Polytetrafluoroethylene stretched porous membrane. Claim 5 In paragraph 1 or 2, the weight per unit area is 7.0 g / m² 2 Polytetrafluoroethylene stretched porous membrane. Claim 6 A polytetrafluoroethylene stretched porous membrane having a thickness of 30 μm or more, according to claim 1 or 2. Claim 7 A breathable filter material having breathability in the thickness direction and preventing the passage of foreign matter in that direction, and comprising a polytetrafluoroethylene stretched porous membrane as described in claim 1 or 2. Claim 8 A breathable filter material according to claim 7, further comprising a breathable support material laminated to the polytetrafluoroethylene stretched porous membrane. Claim 9 A filter member having a breathable filter material that has breathability in the thickness direction and prevents the passage of foreign matter in that direction, wherein the breathable filter material is the breathable filter material described in claim 7. Claim 10 delete

Citation Information

Patent Citations

  • Porous material

    JP1984145124A

  • Low-friction, wear-resistant material and articles made therefrom

    JP2007523247A

  • Method for producing polytetrafluoroethylene porous membrane, wound body, filter medium for filter and method for producing the same

    JP2009024040A